2018
DOI: 10.1080/21645515.2018.1522470
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of active rheumatoid arthritis: comparison of patients younger vs older than 75 years (CORPUS cohort)

Abstract: TNFα antagonists are used less often and glucocorticoids more often in elderly patients with active RA compared to their younger counterparts. The fact that this study was performed in 2007-9 is a limitation in terms of relevance to today's patients and further studies should be conducted in new cohorts of active RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“… 26 bDMARDs were introduced during the collection of the BARFOT cohort, which means that only the patients included during 1999–2006 (about half of the patients) had access to treatment with bDMARDs. As seen in other studies, 11–14 the prescription of bDMARDs was highest for younger patients and decreased with age at onset. GC in monotherapy was used in < 20% of the patients, however, the patients who were most likely to receive this treatment were women and men ≥ 70 years.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“… 26 bDMARDs were introduced during the collection of the BARFOT cohort, which means that only the patients included during 1999–2006 (about half of the patients) had access to treatment with bDMARDs. As seen in other studies, 11–14 the prescription of bDMARDs was highest for younger patients and decreased with age at onset. GC in monotherapy was used in < 20% of the patients, however, the patients who were most likely to receive this treatment were women and men ≥ 70 years.…”
Section: Discussionsupporting
confidence: 84%
“…3 One possible explanation for GC as monotherapy is the occurrence of comorbidities, since RA patients with late onset have a heavier burden of comorbidities compared with younger ones. 11 Notably, GC treatment has been reported to be more common in patients with late onset. 11,12 Access to bDMARDs and targeted synthetic DMARDs have improved the disease outcome immensely and today the treatment aim is clinical remission, or at least low disease activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Age plays a substantial role in sepsis; however, the impact of age on incident infection in patients with RA appears to vary with studies due to the distinct target to treat strategy, use of b/tsDMARDs, and concomitant GCs (20)(21)(22). Increasing evidence has shown that the concern regarding the safety issue of b/tsDMARDs in elderly patients with RA might somehow deprive those patients of optimal disease control and quality of life (20).…”
Section: Discussionmentioning
confidence: 99%